(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The oxidation of benzene by UV-light in the presence of catalyst was studied .It was found that the residual concentration of benzene decreased with the time of irradiation increasing .The complete oxidation was at 180 min. Plot of (LnC) against (t) showed a straight line of pseudo first order reaction .Many solvents such as methanol ethanol , toluene and n-hexane were used in the experiments which explained that the rate constant increased linearly with the polarity of the solvent. ZnO , Cu2O , TiO2 were used in the photo oxidation of benzene as a photo catalysts in addition to the using of Al2O3 .The residual concentration of benzene was the minimized value with TiO2 due to increasing the surface area. Also the increasing in the power of lamp lead to increase the rate of reaction.